Effect of solution-focused approach on anxiety and depression in patients with rheumatoid arthritis: A quasi-experimental study - Zhang, Chunli; Wu, Xuehua; Yuan, Ying; Xiao, Huamei; Li, Erhui; Ke, Hongyan; Yang, Mei; Zhu, Xiaodong; Zhang, Zhicheng (Frontiers in Psychology, 2022)
Abstract: Anxiety and depression are common psychological problems in rheumatoid arthritis (RA) patients. However, few effective nursing intervention models have been designed specifically to reduce these negative emotions in RA patients. Solution-focused approach (SFA) is an effective intervention method for psychosocial issues. This study investigated the effects of SFA-based nursing intervention on anxiety and depression in RA patients. A quasi-experimental study using a convenience sampling of RA patients was conducted. The control group received routine nursing intervention, while the experimental group received SFA-based nursing intervention. The scores on the self-rating anxiety scale (SAS), self-rating depression scale (SDS), arthritis self-efficacy scale-8 (ASES-8), and questionnaire on patient satisfaction with nursing care were collected. There was no statistically significant difference in the SDS, SAS, and ASES-8 scores in the control group before and after routine nursing intervention. However, in the experimental group, the SDS and SAS scores before SFA-based nursing intervention were statistically significantly higher than those after SFA-based nursing intervention, and the ASES-8 score was significantly improved by SFA nursing intervention. Collectively, SFA-based nursing intervention can effectively improve anxiety, depression, and arthritis self-efficacy in RA patients compared to routine nursing intervention. This study broadens clinically psychological models of nursing intervention for RA patients. SFA may be an effective nursing model for various psychosocial problems in the current medical context.